Placement of the Professional Judgment in the Current Remote Working Environment - VIORICA MIRELA STEFAN-DUICU; MIHAELA SUDACEVSCHI (Global Economic Observer)
Current global pandemic changes imposed a new decisional process that drags the reshaping of the professional judgment in the current environment. This reshape is an effect of the pandemic and it is highly correlated to the adaptability of the companies to the new technological path. The continuity of the activity at an organizational level has as base the rethinking of the structure of the professional judgment within remote work conditions. This paper aims to highlight the change of the professional judgment in the new format by explaining the influence and generating factors and, more accurate, the benefits and the drawbacks of the remote work.